The Analysis of Multicultural Based School Development Plans - Nunuk Hariyati (Pascasarjana UM, 2014)
Pengembangan Sekolah Berbasis MultikulturalAbstract: This study aims to determine the process of the preparation and implementation of the school development plan based on a multicultural school. The researcher used a qualitative approach, the type of case study is explanatory. Research location is SPI High School in Kota Batu. The findings of this research indicate that the school has a multicultural RPS, do strategies contained in multicultural RPS, RPS preparation process shown in the flow and RJKM RAKS preparation, implementation of the RPS is good, the school facilitates students in developing good self on the ability of academic and non-academic. Key Words: school development plan (RPS), multicultural education Abstrak: Penelitian ini bertujuan untuk mengetahui proses penyusunan dan implementasi rencana pengembangan sekolah pada sekolah berbasis multikultural. Peneliti menggunakan pendekatan kualitatif, jenis studi kasus, bersifat eksplanatoris. Lokasinya di SMA SPI Kota Batu. Temuan penelitian menunjukkan bahwa sekolah memiliki RPS multikultural, strategi yang dilakukan termuat dalam RPS multikultural, proses penyusunan RPS tampak pada alur penyusunan RAKS dan RJKM, implementasi RPS sudah baik, sekolah memfasilitasi siswa dalam pengembangan diri baik pada kemampuan akademik maupun non akademik. Kata kunci: rencana pengembangan sekolah (RPS), pendidikan multikultural